Design and Analysis of Water Quality Monitoring and Filtration System for Different Types of Water in Malaysia - N. A. Razman; W. Z. Wan Ismail; M. H. Abd Razak; I. Ismail; Juliza Jamaludin (Spinger, 2024)
Indexed by WOS/SCOPUS/ERA